Trieste - Contemporanea 97 : Dialoghi lituani - Dialoghi con l'arte dell'Europa centro orientale. - Cardazzo, Gabriella; Jesurun, Franco; Jurenaite, Raminta; Sabasevicius, Helmutas (Trieste : Trieste Contemporanea, 1997)
Bastys, Darius ; Jonikiené, Lina ; Liskevicius, Dainus ; Lukys, Alvydas ; Lupeikis, Kestutis ; Makarevicius, Gintaras ; Michelkeviciute, Snieguole ; Narkevicius, Deimantas ; Pajarskaité, Grazina ; Rakauskaité, Eglé ; Snipas, Mindaugas ; Matelis, Arunas ; Jevdokimovas, Arturas ; Stonys, Audrius
biografie
Dialoghi lituani, Stazione Marittima, Trieste, 4 - 24 dicembre 1997
Text English-Italian
kunstcatalogus
Keywords: Litouwen